2022
DOI: 10.52589/ajhnm-gniirnmi
|View full text |Cite
|
Sign up to set email alerts
|

Knowledge, Attitude and Practice of Breast Self-Examination in Nigeria: A 10 Year Systematic Review

Abstract: Background: Among the screening methods for the early detection of breast abnormalities that could lead to breast cancer, Breast self-examination is the basic, simplest, cost effective, self-administered and very important technique. It allows women to get acquainted with the nature of their breasts and therefore allows them to discover any deviation. Early detection goes a long way in successful treatment of BC and this is easily come by with good and adequate knowledge, good attitude towards and excellent sk… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 28 publications
0
1
0
Order By: Relevance
“…This integrative review on BSE among female adolescents in Nigeria is of great importance as it focuses only on breast self-examination among female adolescents in Nigeria. In the last ten years, there have been two reviews on BSE in Nigeria but these were focused on the general women population (Ojewusi et al, 2016;Ogunmodede et al, 2022). This current review shows limited published research on BSE among female adolescents in Nigeria.…”
Section: Implication For Researchmentioning
confidence: 90%
“…This integrative review on BSE among female adolescents in Nigeria is of great importance as it focuses only on breast self-examination among female adolescents in Nigeria. In the last ten years, there have been two reviews on BSE in Nigeria but these were focused on the general women population (Ojewusi et al, 2016;Ogunmodede et al, 2022). This current review shows limited published research on BSE among female adolescents in Nigeria.…”
Section: Implication For Researchmentioning
confidence: 90%
“…Despite the high incidence of BC in Nigeria, studies have shown a lack of awareness and knowledge about the risk factors and symptoms of BC among Nigerian women in respective of locations, and this invariably contributes to delayed diagnosis and poorer treatment outcomes. [8][9][10] Though the world health organization emphasizes that adhering to existing evidence-based preventive strategies and minimizing exposure to modifiable risk factors can prevent between 30% and 50% of cancer deaths, many women in reproductive age group often neglect preventive measures and early screening due to various cultural, social, and economic barriers. 11,12 As a result, BC is often diagnosed at advanced stages when treatment options are limited, leading to higher mortality rates.…”
mentioning
confidence: 99%